Implementasi Aplikasi Informasi Kajian Islami di Masjid Nurul Iman - Dedi Gunawan; Abdullah; Dzaky Haidar; Muhammad Bayram AT; Rizqi Kurniawan Saputra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
All Muslims must impart the great laws of Islam to all mankind so that they can feel peace and tranquility. In addition to the obligation to preach, Islam requires followers to study the religion. The more religious knowledge we have, the better we fear Allah and protect ourselves from disobedience. Because with religious knowledge, we can know what is good and what is bad. is not. Second, the potential for technological development, especially in Indonesia, is driven by several factors, such as the heavy use of the Internet, the increase in Islamic Websites on the Internet, and live streaming of Islamic studies, especially at Majid Nurul Iman Blok M. Supported. The development of this research information system application was designed based on community needs obtained through research methods, interviews, and questionnaires. During the design phase, use case and activity diagrams are used to describe the relationships that occur in each flow, data flow diagrams are used to determine user access levels (superadmin vs. admin), and ERDs are Used for database design. In the final stage, the test uses usability testing to get her SUS score. Here we measure the feasibility of finding problems and applying the information systems of this study according to the needs of the community. Finally, we can conclude that the development of this research information system application can be used according to the needs of the community. As such, this service activity can provide benefits and convenience to Muslims in acquiring religious knowledge.